A Proposal for the Establishment of Small Claims Courts in Chile - (:unkn) unknown (My University, 2016)
The public perception of civil and commercial justice in the Chilean courts is notfavorable. Common criticisms include concerns with an antiquated code that is notresponsive to current demands, complex written procedures that consume seeminglyinfinite amounts of time and resources, and rules of evidence that are perceived asincompatible with today’s digital world.